The relationship of skill level to anterior cruciate ligament injury - Harmon, K. G.; Dick, R. (Clinical Journal of Sport Medicine, 1998)
OBJECTIVE: To examine the relationship of skill, as represented by NCAA division level, to anterior cruciate ligament rupture in collegiate men's and women's basketball and soccer players. DESIGN: Randomized, retrospective. PARTICIPANTS: Women's and men's basketball and soccer players at NCAA Division I, II, and III institutions. MAIN OUTCOME MEASURE: Athletes with or without ACL injury. RESULTS: There was no relationship of ACL injury rate to NCAA division level in men's or women's basketball or soccer. CONCLUSIONS: There are many different variables that contribute to a player's skill level. Although these variables may relate to ACL injury and may be responsible for the differential in injury rate between men and women, skill level as represented by collegiate division does not relate to ACL injury. When considering possible etiologies of the differential in ACL injury rates between men and women, the use of the term "skill" should be avoided, and more specific terms used. Clin J Sport Med 1998 Oct;8(4):260-5